PERENCANAAN DAN PERANCANGAN TERMINAL PELABUHAN PENUMPANG DI DESA KUSAMBA: Bahasa Indonesia - I Putu Egatama Arya Putra; I Wayan Parwata; I Wayan Widanan; Ni Putu Ratih Pradnyaswari Anasta Putri (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2025)
This planning is based on an increase in the number of tourists coming to Bali every year, namely 2.2 million tourists in 2022 and increasing by 114 percent in 2023 with a total of 5.3 million tourists. Kusamba village, Dawan subdistrict, Klungkung regency is a strategic area and very close to Nusa Penida and Nusa Lembongan which makes this village a place for sailing boats wishing to cross to the island, therefore most of the Kusamba community depends on the tourism sector. This data shows that there is great potential for business opportunities for the surrounding community. The aim of this research is to plan and design passenger-specific port terminal facilities to solve current problems. Carrying the concept of